2019
DOI: 10.1101/663419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GABAergic cell loss in mice lacking autism-associated geneSema6A

Abstract: Background: During brain development, a multitude of neuronal networks form as neurons find their correct position within the brain and send out axons to synapse onto specific targets. Altered neuronal connectivity within these complex networks has been reported in Autism Spectrum Disorder (ASD), leading to alterations in brain function and multisensory integration. Semaphorins (also referred to as Semas), a large protein family of about 30 members, have been shown to play an important role in neuronal circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…25,26 Furthermore, Sema6A contributes to GABAergic interneuron migration during brain development, and its disruption might be an underlying cause of autism spectrum disorder (ASD). 27 In addition, this pathophysiological mechanism might be shared with epilepsy. 27,28 Consistent with this hypothesis, SEMA6B was expressed in GABAergeic neurons (Figure S6B), and disruption of SEMA6B function in GABAergic neurons might contribute to epilepsy in humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Furthermore, Sema6A contributes to GABAergic interneuron migration during brain development, and its disruption might be an underlying cause of autism spectrum disorder (ASD). 27 In addition, this pathophysiological mechanism might be shared with epilepsy. 27,28 Consistent with this hypothesis, SEMA6B was expressed in GABAergeic neurons (Figure S6B), and disruption of SEMA6B function in GABAergic neurons might contribute to epilepsy in humans.…”
mentioning
confidence: 99%
“…27 In addition, this pathophysiological mechanism might be shared with epilepsy. 27,28 Consistent with this hypothesis, SEMA6B was expressed in GABAergeic neurons (Figure S6B), and disruption of SEMA6B function in GABAergic neurons might contribute to epilepsy in humans. Our zebrafish sema6ba/b-ex.17-injected crispants demonstrated increased PTZ-mediated hyperactive responses compared with the response of the sema6ba/ b-ex.2-injected larvae.…”
mentioning
confidence: 99%
“…This gene, in particular, has been evaluated as being involved in the development of neuronal networks, regulated by intracellular signaling events; furthermore, altered neuronal connectivity is reported in individuals with ASD [99][100][101][102][103]. Menzel et al (2019), through the use of genetically modified mice, observed how the knockout of SEMA6A is relevant for the formation of GABAergic interneurons in several brain areas involved in ASD, such as the primary somatosensory cortical areas, the hippocampus, and the Thalamic Reticular Nucleus (RTN), consequently leading to alterations in excitatory/inhibitory (E/I) balance and neurodevelopmental defects/ASD [99]. Considering that our data show an overexpression of SEMA6A, it is reasonable to think that it may have an important role in the phenotype of subjects with ASD, as proposed by the authors mentioned above.…”
Section: Go Terms In the "Na_pos" Phenotype 421 Gocc_neuron_projectionmentioning
confidence: 99%